2016
DOI: 10.3163/1536-5050.104.2.008
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in affiliation indexing in Scopus and PubMed

Abstract: Methods: First, we compared Scopus affiliation identifier search results to PubMed affiliation keyword search results. Then, we searched Scopus using affiliation keywords (UNMC, etc.) and compared the results to PubMed affiliation keyword and Scopus affiliation identifier searches. Results: We found that Scopus's records for approximately 7% of UNMC/NM authors' publications lacked appropriate UNMC/NM author affiliation identifiers, and many journals' publishers were supplying incomplete author affiliation info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…In the analyzed data, which were exported from Scopus, 75 (4.9%) publications did not have the address of their authors' affiliation registered, thus not allowing the counting of those countries that had 197 citations. This finding of not filling in the affiliation of the authors of these 75 documents corroborates the study presented by Schmidt et al (2016), who identified that approximately 7% of the publications in the sample analyzed by the researchers did not have identifiers for author affiliation.…”
Section: Analysis Of Most Active Countriessupporting
confidence: 90%
“…In the analyzed data, which were exported from Scopus, 75 (4.9%) publications did not have the address of their authors' affiliation registered, thus not allowing the counting of those countries that had 197 citations. This finding of not filling in the affiliation of the authors of these 75 documents corroborates the study presented by Schmidt et al (2016), who identified that approximately 7% of the publications in the sample analyzed by the researchers did not have identifiers for author affiliation.…”
Section: Analysis Of Most Active Countriessupporting
confidence: 90%
“…Furthermore, understanding the inherent characteristics of highly cited studies may help researchers interested in publishing. 56 Limitations. The main limitations are related, on the one hand, to the data source used, and, on the other hand, to the thematic dispersion of the journals where the research results of professionals in the area are published.…”
Section: Discussionmentioning
confidence: 99%
“…Robustness of our data depends greatly on the soundness of the individual Scopus author and article records, which are not self-reported. This is a strength of the study, because we are using a standardised and internationally recognised data source for scientific productivity, but it is also a limitation, as there could be potential errors in the Scopus dataset that we would not be able to correct for 41. Nevertheless, Scopus disambiguates author names in the Scopus Author Profile, which is automatically created by Scopus using a sophisticated algorithmic profiling that Scopus itself admits is not 100% accurate 42.…”
Section: Discussionmentioning
confidence: 99%